Effect of stone powder on the rheological and mechanical performance of cement-stabilized marine clay/sand. (30th November 2020) - Bayesteh, Hamed; Sharifi, Mahdi; Haghshenas, Ali
Highlights: The grout workability in order to increase the strength of the soilcrete was evaluated. An economical additive was proposed to increase soilcrete strength in marine clay/sand that maintains grout workability. The addition of 20% stone powder eliminated the negative effects of the water. Abstract: The application of soil-cement (soilcrete) columns created by jet grouting for the improvement of marine sediment has increased. An increase in the soilcrete strength using this method is a goal of engineers. One requirement of the jet grouting method is the ability to inject grout through nozzles with small diameters. Conventional methods of increasing soilcrete strength, such as reducing the water-to-cement ratio or using additives, are not applicable to jet grouting because they increase the viscosity of the grout and decrease its workability; thus, it is necessary to study grout workability (rheological properties) in order to increase the strength (mechanical properties) of the soilcrete. Previous research has focused on either the mechanical or rheological behavior of soilcrete. The current study used an appropriate and economical additive to increase soilcrete strength in marine clay/sand that maintains grout workability. Stone powder was selected as a cost-effective additive and superplasticizer was added to achieve proper performance. Cement was added at 20% by dry weight of soil at water-to-cement ratios of 0.75, 1 and 1.25 and the addition of 0%, 20%, 30% and 40% of stone powder. The results showed that the water/cement ratio had a significant effect on the workability and strength of the samples. The addition of 20% stone powder eliminated the negative effects of the water and increased the strength of the sand-cement samples, but had little effect on the clay-cement strength. The highest strength obtained in clay-cement samples was 5.2 MPa at W/C = 0.75 and SP = 0.7%. The highest strength obtained in sand-cement samples was 7 MPa at W/C = 1 with 20% stone powder. It is also showed good workability; thus, this mixing method is recommended for sand-cement based columns.